1982
DOI: 10.1207/s15327752jpa4606_3
|View full text |Cite
|
Sign up to set email alerts
|

Primary Process Patterning in College Students' Inkblot Responses

Abstract: Holzman Inkblots were administered under standard instructions and under instructions to respond imaginatively. Protocols were scored according to Holt's system for scoring primary process. Subcategories of primary process proved to be reliable and to differ in prominence. A stable pattern of primary process, characterizing college students' inkblot responses, appears to represent students' intuition of what it means to be imaginative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, how HIT variables are coded leads to a loss of information. Previous research highlighted the utility of the HIT as a research tool and coped with this limitation by either applying the Rorschach coding system to HIT protocols or creating new variables using a HIT coding system ( Endicott and Jortner, 1966 ; Bowers and van der Meulen, 1970 ; Cooper and Caston, 1970 ; Bowers, 1971 ; Lefcourt et al, 1972 ; Domino, 1980 ; Lockwood et al, 1981 ; Rosegrant, 1982 ; Prokop, 1983 ; O’Neill et al, 1984 ). In line with this approach, we used the HIT variables and their scores to develop more sophisticated indices, taking inspiration from Exner’s Comprehensive System.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how HIT variables are coded leads to a loss of information. Previous research highlighted the utility of the HIT as a research tool and coped with this limitation by either applying the Rorschach coding system to HIT protocols or creating new variables using a HIT coding system ( Endicott and Jortner, 1966 ; Bowers and van der Meulen, 1970 ; Cooper and Caston, 1970 ; Bowers, 1971 ; Lefcourt et al, 1972 ; Domino, 1980 ; Lockwood et al, 1981 ; Rosegrant, 1982 ; Prokop, 1983 ; O’Neill et al, 1984 ). In line with this approach, we used the HIT variables and their scores to develop more sophisticated indices, taking inspiration from Exner’s Comprehensive System.…”
Section: Discussionmentioning
confidence: 99%
“…Not only did the intercorrelation matrix show highly significant positive correlations between corresponding Forma A and B variables but also all variables showed an increase in their scores during the physical activity in comparison with before the exercise. Several authors in past decades have applied Rorschach scoring variables to HIT protocols with good results ( Megargee and Cook, 1967 ; Bowers and van der Meulen, 1970 ; Bowers, 1971 ; Lefcourt et al, 1972 ; Domino, 1980 ; Lockwood et al, 1981 ; Rosegrant, 1982 ; Prokop, 1983 ; O’Neill et al, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both remain unchanged despite the empir ical literature. Rosegrant (1982) contributed to the con struct validity of Holt's system for scoring primary process manifestations, while Sison et al (1981) showed correlations between HIT variables and three of the Mosher Guilt Scales. In a potentially useful study, Stumer et al (1980) reported that a stressful situation induced an increase in "emotional indicators" in children.…”
Section: Human Figure Ora Wingsmentioning
confidence: 96%
“…For the Holtzman et al (1961), each protocol was estimated to have 1 response for each card administered unless stated otherwise. We excluded four studies because they contained reliability coefficients too ambiguous to definitively code (Benfari & Calogeras, 1968; Rosegrant (1982) .91 r S 2 A1 Some training Nonpatient 20 P Saunders (1991) .70 r S 2 Ag Some training Violent off (10) P Wiseman & Rehyer (1973) .89 r S 2 Ag Some training Violent off 10 P Dissertations Caldwell (1993) .52 kappa R 2 A1 Unknown Nonpatient (400) R Greco (1989) . Note.…”
Section: Data Analysesmentioning
confidence: 99%